Application of The Independent Curriculum In Jurisprudence Learning In The Industrial Revolution Era 4.0 - Nikmah, Faridhatun (Fahmina: Jurnal Pendidikan Islam, 2024)
The era of the industrial revolution 4.0 brought many changes in various areas of life. One of them is the field of education, not only in the general field that has changed, but also in the field of Islamic education, such as Jurisprudence. These changes include curriculum and technology changes that are increasingly rapid. Currently, Indonesia has implemented an independent curriculum that aims to provide opportunities for students to explore and develop talents and interests. This study aims to determine the implementation of the independent curriculum in fiqh learning at MA Al-Muayyad Surakarta and to determine the suitability of the application of the fiqh curriculum in the era of the industrial revolution 4.0. The method used in this study is descriptive qualitative by describing the data found in the field which is then reinforced with relevant theories. The results of this study show that the implementation of the curriculum applied at MA Al-Muayyad Surakarta includes learning preparation, learning implementation, and learning evaluation. The suitability of application in the era of revolution 4.0 is appropriate, but not optimally. This is due to the lack of facilities that support the theme in learning.